Video Yardımlı Torakoskopik Cerrahi Yapılan Akciğer Kanserli Hastalarda Pulmoner Rehabilitasyonun Solunum Fonksiyonları Egzersiz Kapasitesi ve Yaşam Kalitesi Üzerine Etkisi - Altunsoy, Nur Betül (My University, 2024)
Daha sonra doldurulacaktır

Daha sonra doldurulacaktır
The Effectiveness of Pulmonary Rehabilitation on Pulmonary Functions, Exercise Capacity, and Quality of Life in Patients With Lung Cancer Undergoing Video Assisted Thoracoscopic Surgery (VATS)
Keywords: Fizyoterapi ve Rehabilitasyon; Göğüs Cerrahisi; Onkoloji; Physiotherapy and Rehabilitation; Thoracic Surgery; Nefes Egzersizleri; Oncology; Breathing Exercises; Pulmoner Rehabilitasyon; Pulmonary Rehabilitation